2017
DOI: 10.1371/journal.pone.0178253
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 is a novel biomarker for diabetic retinopathy and inhibits HGHL-induced VCAM-1 expression in an AMPK-dependent manner

Abstract: ObjectivesDiabetic retinopathy (DR) is a severe complication of chronic diabetes. The C1q/TNF-related protein family (CTRPs) has been demonstrated to exert protective effects against obesity and atherosclerosis in animal studies. Heretofore, the association between circulating CTRPs and DR patients has been unexplored. In the current study, we attempt to define this association, as well as the effect of CTRPs upon DR pathophysiology.DesignThe present investigation is a case control study that enrolled control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
2
44
0
1
Order By: Relevance
“…The expenditure of each indexes were calculated, based on the website of Beijing Medical Service [13].…”
Section: Expenditure Of Indexesmentioning
confidence: 99%
“…The expenditure of each indexes were calculated, based on the website of Beijing Medical Service [13].…”
Section: Expenditure Of Indexesmentioning
confidence: 99%
“…CTRP6, although it has no effect on collagen or fibroblasts proliferation, does suppress in response to alterations in energy state and predicting changes in the metabolic circuit [21] . Therefore, among the CTRPs, CTRP1 displays the potential to serve as a marker and therapeutic target in the vascular system and CTRP3 exhibits biomarker features in patients with diabetic-related PDR [45] . CTRP5 appears to have a greater potential to serve as a biomarker to predict the risks in PCI following the clinical operations.…”
Section: Ctrps and Cardiovascular Systemmentioning
confidence: 99%
“…HG exposure of glomerular MCs can activate the JAK2/STAT3 signaling cascades, thus stimulating excessive proliferation and growth of glomerular MCs. [15][16][17] Recently, one study showed that blood levels of CTRP3 are decreased in diet-induced obese mice, and recombinant CTRP3 infusion could suppress blood glucose in wild-type, obese, and diabetic mice. This family is involved in the pathogenesis of various diseases, including atherosclerosis, liver disease, insulin resistance, and kidney disease.…”
Section: Introductionmentioning
confidence: 99%